2000
DOI: 10.1093/emboj/19.6.1290
|View full text |Cite
|
Sign up to set email alerts
|

BDNF regulates eating behavior and locomotor activity in mice

Abstract: contributed equally to this work Brain-derived neurotrophic factor (BDNF) was studied initially for its role in sensory neuron development. Ablation of this gene in mice leads to death shortly after birth, and abnormalities have been found in both the peripheral and central nervous systems. BDNF and its tyrosine kinase receptor, TrkB, are expressed in hypothalamic nuclei associated with satiety and locomotor activity. In heterozygous mice, BDNF gene expression is reduced and we find that all heterozygous mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
623
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(670 citation statements)
references
References 59 publications
(79 reference statements)
41
623
1
5
Order By: Relevance
“…The second marker is brain-derived neurotrophic factor (BDNF), which was found previously to mark ventrolateral VMN neurons in adult mice (Kernie et al, 2000). Using mutant mice that harbor lacZ in the BDNF locus (BDNF lacZ ), we observed prominent expression of BDNF lacZ (β-galactosidase) in the ventrolateral region of the anterior and medial VMN of adult mice that overlapped significantly with SF-1, especially in the anterior VMN (Fig.…”
Section: Altered Expression Of Early and Late Vmn Markers In Sf-1 −/−mentioning
confidence: 65%
See 1 more Smart Citation
“…The second marker is brain-derived neurotrophic factor (BDNF), which was found previously to mark ventrolateral VMN neurons in adult mice (Kernie et al, 2000). Using mutant mice that harbor lacZ in the BDNF locus (BDNF lacZ ), we observed prominent expression of BDNF lacZ (β-galactosidase) in the ventrolateral region of the anterior and medial VMN of adult mice that overlapped significantly with SF-1, especially in the anterior VMN (Fig.…”
Section: Altered Expression Of Early and Late Vmn Markers In Sf-1 −/−mentioning
confidence: 65%
“…However, the obesity phenotype observed in BDNF +/− mice results from hyperphagia and shows incomplete penetrance. Obese BDNF +/− mice exhibit normal locomotor activity, whereas nonobese BDNF +/− mice are thought to counteract this hyperphagia through hyperactivity (Kernie et al, 2000). More recently, conditional inactivation of BDNF in adult mice also resulted in hyperactivity associated with increased anxiety-like behavior (Rios et al, 2001).…”
Section: Sf-1 and Bdnf In Feeding And Locomotor Behaviorsmentioning
confidence: 99%
“…BDNF-deficient mice exhibited increased eating behavior that was transiently reversed when BDNF was infused. 27 Thus, increased TrkB expression or TrkB-mediated signaling may serve as a negative regulatory pathway involved in food 28 This study has a number of strengths and limitations. We used a relatively large number of SNP markers to capture as much variation as possible across NTRK2.…”
Section: Discussionmentioning
confidence: 99%
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
“…Furthermore, similarly to methadone-maintained patients (Willenbring et al, 1989;Zador et al, 1996), exaggerated opioidergic activity could enhance hedonic preference (ie, liking) for sweet and fatty foods (Doyle et al, 1993;Pecina and Berridge, 1995;. The consumption of these foods further reduces BDNF efficiency in preventing neuronal death (Molteni et al, 2002) and in regulating reward function (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003), glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000), appetitive behaviors (Eisch et al, 2003;Itoh et al, 2004), and other important homeostatic processes (Xu et al, 2003).…”
Section: Abnormal Opioidergic Function May Impair Liking Processes Inmentioning
confidence: 99%